State Creation and Revenue Allocation in Nigeria: a political economy perspective (2022)
This book is based on welfare economics which tends to correct the failures of the free market in efficient allocation and distribution of resources as well as economic stability and growth.
Includes bibliography
osc 14/01/2024
Loans
Keywords: Revenue Allocation; State creation; Nigeria